PENGUATAN NILAI-NILAI KEAGAMAAN SISWA MELALUI PENDEKATAN DEEP LEARNING DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 34 MUARO JAMBI - Muqoddas, Ahmad; Fahri, Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the strengthening of students’ religious values through the Deep Learning approach in Islamic Religious Education (IRE) at SMP Negeri 34 Muaro Jambi. The research addresses the issue of students’ learning practices that tend to emphasize surface learning, resulting in limited internalization of religious values. The purpose of this study is to describe the planning process, implementation, and supporting and inhibiting factors of the Deep Learning approach in strengthening students’ religious values. This research employed a qualitative descriptive method. Data were collected through participant observation, semi-structured interviews, and documentation involving the school principal, IRE teachers, and eighth-grade students. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The findings show that the Deep Learning approach was implemented through the principles of mindful, meaningful, and joyful learning, which encouraged students to actively engage in reflection, contextual understanding, and practical application of religious values in daily activities. Religious values such as honesty, responsibility, discipline, and social awareness were observed to be more consistently integrated into learning activities. Supporting factors included teacher understanding of the approach, alignment with the school’s vision, and a supportive learning environment, while inhibiting factors involved limited instructional time and differences in students’ learning readiness. Overall, the study indicates that the Deep Learning approach contributes to making Islamic Religious Education learning more meaningful in strengthening students’ religious values.